Infus liquid monitoring system using web-based loadcell sensor - Riandi Gustiawan Gustiawan; Fajar Kholid; Sa'id Ainul Yaqin; Dekki Widiatmoko; Kasiyanto (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
Improvements in the efficiency and precision of using the Internet of Things (IoT) to monitor infusion fluid volumes have been particularly beneficial to the health sector. It is now feasible to create intelligent solutions that replace labor-intensive and error-prone manual techniques with the aid of affordable devices like the ESP8266 and accurate sensors. Through the use of an internet connection, the server may easily receive data on the volume of infusion fluids collected by the ESP8266-based system and precision sensors. This enables remote access to real-time monitoring using a web platform. The main advantage of this technology is that it allows medical personnel to adequately monitor patients even when they are nearm not them. This reduces patient distraction and gives patients more time to focus on important medical tasks. By using this technology, healthcare personnel can improve the quality of treatment they give by reducing the chance of human error when calculating and changing IV bags. When medical staff has access to dependable and real-time data updates, they can manage IV fluid management more skillfully and respond to changes in patient situations more quickly. All things considered, these advancements represent significant strides forward in the administration of intravenous fluids, offering more accurate, effective, and conveniently accessible solutions that elevate the bar for healthcare overall